P202 Assessment of bronchiectasis scoring systems: a long term cohort study. (12th November 2015) - Ellis, HC; Cowman, S; Fernandes, M; Wilson, R; Loebinger, MR
Abstract : Introduction: Bronchiectasis is a chronic, disabling illness with an unpredictable clinical course. Two multidimensional scores have been developed to predict mortality in bronchiectasis: the bronchiectasis severity index (BSI) and the FACED score. 1, 2 This study is a retrospective cohort study aiming to compare these scores and test their ability to predict long-term mortality in bronchiectasis. Methods: Data was obtained for 74 subjects with bronchiectasis who had previously taken part in research at our centre. BSI and FACED scores were calculated and outcomes were ascertained after a median of 18.8 years follow-up. Receiver operator characteristic (ROC) curves for mortality were generated and survival between groups compared using univariate Cox proportional hazards analysis. Results: Both scoring systems had similarly excellent predictive power for 5-year mortality, with area under the ROC curve (AUC) 0.79 for BSI and 0.8 for FACED. Both scores were also able to predict 15-year mortality (Figure 1 ), with the FACED score showing superior predictive power (AUC 0.82 vs 0.69 P = 0 .0495). For both scores subjects with high scores had an increased risk of death compared to the low scoring group (hazard ratio (HR) for death 3.6 for BSI P = 0 .02, 12.5 for FACED P < 0 .001). The intermediate scoring FACED group was also at an increased risk of death (HR 5.9 P < 0.001), whereas the intermediate BSI group was not (HR 1.4 P = 0 .58). The BSI tended to assign higher scores; accordingly the high BSI group was larger (33 vs 6 subjects) with a lower mortality (57% vs 83%) than the equivalent FACED group. Conclusion: This study demonstrates the ability of the BSI and FACED score to predict mortality in bronchiectasis over a far longer period than previously described. Such tools will be valuable for stratification in clinical trials and for identifying individuals in a higher risk group for intensified treatment. References: 1 Chalmers JD, Goeminne P, Aliberti S, et al. The bronchiectasis severity index. An international derivation and validation study. Am J Respir Crit Care Med . 2014;189 :576–85 2 Martínez-García MÁ, de Gracia J, Vendrell Relat M, et al . Multidimensional approach to non-cystic fibrosis bronchiectasis. The FACED score. Eur Respir J . 2014;43 :1357–1367